(untitled) (Construction Economics and Building, 2014)
This paper proposes a model for entry location (EL) and entry timing (ET) decisions to guide construction firms in accessing targeted international markets. Neglecting to properly choose the right combination of the entry location and entry timing (ELET) decisions can lead to poor performance of the firms’ international ventures. The sampling frame was from the Malaysian construction firms that have undertaken and completed projects abroad. Survey questionnaires sent to 115 firms registered with Construction Industry Development Board (CIDB) Malaysia, operating in more than 50 countries, achieved a 39.1 per cent response rate. Based on a comprehensive statistical analysis of survey data it was found that the mutually inclusive significant factors that influenced the firms’ ELET decisions were: the firm’s ability to assess market signals and opportunities, international experience, financial capacity, competencies and capabilities (project management, specialist expertise and technology), resources (level of knowledge based on research and development), experience in similar works, financial support from the home country banks, technical complexities of projects and availability of funds for projects. Hence, the present research builds on and extends the literature on the ELET decisions in a more integrated way. Keywords: Entry location, entry timing, resource-based view, international markets, Malaysian construction firms.